A Case of Infective Endocarditis and Spinal Epidural Abscess Caused by Streptococcus mitis Bacteremia. (5th September 2017) - Byrd, Victoria S.; Nemeth, Attila S.
Abstract : A 57-year-old man presented with abdominal pain, hematemesis, and melena. He reported taking high-dose ibuprofen for back pain and drinking several 24-ounce beers daily. Examination was remarkable for icteric sclera, poor dentition, tachycardia, and crescendo-decrescendo murmur at right upper sternal border, radiating to the carotids. Labs revealed leukocytosis, anemia, thrombocytopenia, and elevated liver function tests and INR. Endoscopy demonstrated antral ulcers, duodenitis, and esophagitis. Blood cultures were obtained and broad-spectrum antibiotics started; cultures later grew Streptococcus mitis, and antibiotic coverage was narrowed. Transthoracic echocardiogram (TTE) demonstrated aortic stenosis and regurgitation, but no vegetation. Repeat blood cultures were negative; however, the patient developed neurological symptoms concerning for cauda equina syndrome, and MRI revealed epidural abscess. Emergent decompression could not be performed as the patient developed hematemesis and required intubation. Transesophageal echocardiogram (TEE), initially deferred due to friable esophageal mucosa, was performed and revealed small aortic valve vegetation. Poor oral hygiene was felt to be the probable source of the patient's S. mitis bacteremia, epidural abscess, and infective endocarditis. The patient's neurological symptoms resolved without intervention and remaining teeth were extracted. This case demonstrates that Streptococcus mitis can result in clinically significant bacteremia, particularly in immunocompromised patients, including chronic heavy alcohol users.